COVID-19 in pregnancy: the foetal perspective—a systematic review - Rajani Dube; Subhranshu Sekhar Kar (BMJ Paediatrics Open)
Objective We aimed to conduct a systematic review of the available literature to determine the effects of confirmed cases of COVID-19 in pregnant women from the foetal perspective by estimation of mother to child transmission, perinatal outcome and possible teratogenicity.Methods Data sources: eligible studies between 1 November 2019 and 10 August 2020 were retrieved from PubMed, Embase, LitCovid, Google Scholar, EBSCO MEDLINE, CENTRAL, CINAHL, MedRXiv, BioRXiv and Scopus collection databases. English language case reports, case series and cohort studies of SARS-CoV-2 confirmed pregnant women with data on perinatal outcome, congenital anomalies and mother to child transmission were analysed.Results 38 case reports, 34 cohort and case series describing 1408 neonates were included for evidence acquisition of mother to child transmission. 29 case reports and 31 case series and cohort studies describing 1318 foetuses were included for the evaluation of perinatal outcome and congenital anomalies. A pooled proportion of 3.67% neonates had positive SARS-CoV-2 viral RNA nasopharyngeal swab results and 7.1% had positive cord blood samples. 11.7% of the placenta, 6.8% of amniotic fluid, 9.6% of faecal and rectal swabs and none of the urine samples were positive. The rate of preterm labour was 26.4% (OR=1.45, 95% CI 1.03 to 2.03 with p=0.03) and caesarean delivery (CS) was 59.9% (OR=1.54, 95% CI 1.17 to 2.03 with p=0.002). The most common neonatal symptom was breathing difficulty (1.79%). Stillbirth rate was 9.9 per 1000 total births in babies born to COVID-19 mothers.Conclusion Chances of mother to child transmission of the SARS-CoV-2 virus is low. The perinatal outcome for the foetus is favourable. There is increased chances of CS but not preterm delivery.The stillbirth and neonatal death rates are low. There are no reported congenital anomalies in babies born to SARS CoV-2 positive mothers.